Fox - Fordyce Disease, a Case Report: Prurito Vulvar y Enfermedad de Fox – Fordyce, un reporte de caso - Contreras Gala, Katherine Luisa (2020)
Fox-Fordyce disease is a non-infectious, infrequent inflammatory dermatosis of apocrine glands, isolated by a pruritic papular rash that usually begins frequently at puberty, and which may involve vulva, armpit and perianal region. It affects women more frequently, approximately in a 9 to 1 ratio, compared to men. In the presentation of the case of a female patient, 53 years old, in consultation of Gynecology-Obstetrics, of the General Maria Auxiliadora Hospital, for presenting for 5 months, papular eruption in vulvar area, associated with intermittent pruritus. A biopsy of the lesion was requested, and it was sent to the Pathological Anatomy Service, receiving a fragment of dark brown tissue, 0.3 x 0.2 x 0.1cm, which was automatically processed, obtaining a histological sheet, in which evidence dilated apocrine glands, which show a thick secretion made up of mucin, in its light. The patient met the histopathological criteria for the diagnosis of Fox - Fordyce disease. Consider the case presentation because of the infrequent nature of this disease